Developing English Learning Materials through Character-Based Intstructional Materials with Card Media - Rizki Fiprinita; Roswati Roswati; Idham Syahputra; Nurdiana Nurdiana (J-SHMIC : Journal of English for Academic, 2020)
Abstract The integration between English language learning and character values is paramount to improve student achievements include cognitive, psychomotor, and affective. Yet, the implementation of this integration has insufficient results. Therefore, this research aimed to develop English learning materials integrated with character values. The research design was research and development (RnD) developed by Borg and Gall and modified by Sugiyono with 4-D (define, design, develop, and disseminate) model. The research was conducted at grade VII of State Junior High School 4 Pekanbaru. The techniques of collecting data were questionnaire, interviews, and observation. The module was validated by experts and practitioners. The data were analyzed both quantitative and qualitative by concerning 3 aspects: content (english learning materials and character values), media design, and practicality. Based on research findings, the module was practical (79%) and very valid in terms of media design (86%) and content (95%). Hence, this module can be used as an assisting tool for students not only to understand and practice the language, but also develop their attitude in communication.